RELATIONSHIP BETWEEN COPING STRATEGIES AND ANXIETY AMONG THIRD TRIMESTER PREGNANT WOMEN - Cut Aulia Azzahra; Eridha Putra; Rahmisyah Rahmisyah (Journal of World Future Medicine, Health and Nursing, 2026)
This study aims to examine the relationship between coping strategies and anxiety levels among third-trimester pregnant women at Baitussalam Public Health Center, Aceh Besar Regency. This research employed a quantitative analytic design with a cross-sectional approach, selected for its efficiency in measuring associations between variables at a single point in time. The population consisted of 67 pregnant women, and a sample of 40 respondents was selected using the Slovin formula with a 10% margin of error, through purposive sampling. Data were collected using the Brief COPE questionnaire to assess coping strategies and the Hamilton Anxiety Rating Scale (HARS) to measure anxiety levels, both of which have demonstrated good validity and reliability in prior studies. The results showed that 65.0% of respondents used adaptive coping strategies, while 35.0% applied maladaptive coping. In terms of anxiety, 45.0% of respondents reported no anxiety, whereas 55.0% experienced varying levels of anxiety, predominantly mild. Statistical analysis using the Chi-square test revealed a significant relationship between coping strategies and anxiety levels (p = 0.009). The novelty of this study lies in highlighting the role of coping strategies as a key psychological determinant in maternal mental health during late pregnancy in a local Indonesian setting. The findings imply that strengthening adaptive coping through antenatal education and psychosocial support can effectively reduce anxiety and improve maternal well-being. This study contributes to the development of maternal health science, particularly in integrating psychological aspects into comprehensive antenatal care services.